Pembelajaran Kooperatif Model Role Playing untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran PPKN di SMP Negeri 1 Pemenang - Siti Maani (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to describe the implementation of the Role Playing model of cooperative learning in increasing student interest in learning in Civics subjects at SMPN 1 Pemenang. This research method uses classroom action research. The research subjects were students of class VIII.1 with a total of 23 people. The research instrument used observation sheets and documentation and then the data were analyzed descriptively. The results showed that in the first cycle the average student learning activity was only 70.33%, so that students who had completed only reached 74.82% and those who had not completed reached 16.52%. In the second cycle the average student learning activity increased to 85.55%, students who completed to 89.96% and students who did not complete decreased to 7.88%. Based on these data, it can be concluded that the application of the Role Playing model of cooperative learning methods can increase student interest in learning in Civics subjects at SMPN 1 Pemenang.